Pregunta
upstudy study bank question image url

Solve the system by the addition method. \( \begin{array}{l}3 x-4 y=3 \\ 5 x+3 y=-24\end{array} \) Select the correct choice below and, if necessary, fill in the answer box to complete your choice. A. The solution set is \{ \}. (Type an ordered pair.) B. There are infinitely many solutions.

Ask by Johnston Delgado. in the United States
Feb 26,2025

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

The solution set is \((-3, -3)\).

Solución

Solve the system of equations \( 3x-4y=3;5x+3y=-24 \). Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}3x-4y=3\\5x+3y=-24\end{array}\right.\) - step1: Solve the equation: \(\left\{ \begin{array}{l}x=\frac{3+4y}{3}\\5x+3y=-24\end{array}\right.\) - step2: Substitute the value of \(x:\) \(5\times \frac{3+4y}{3}+3y=-24\) - step3: Simplify: \(\frac{5\left(3+4y\right)}{3}+3y=-24\) - step4: Multiply both sides of the equation by LCD: \(\left(\frac{5\left(3+4y\right)}{3}+3y\right)\times 3=-24\times 3\) - step5: Simplify the equation: \(15+29y=-72\) - step6: Move the constant to the right side: \(29y=-72-15\) - step7: Subtract the numbers: \(29y=-87\) - step8: Divide both sides: \(\frac{29y}{29}=\frac{-87}{29}\) - step9: Divide the numbers: \(y=-3\) - step10: Substitute the value of \(y:\) \(x=\frac{3+4\left(-3\right)}{3}\) - step11: Calculate: \(x=-3\) - step12: Calculate: \(\left\{ \begin{array}{l}x=-3\\y=-3\end{array}\right.\) - step13: Check the solution: \(\left\{ \begin{array}{l}x=-3\\y=-3\end{array}\right.\) - step14: Rewrite: \(\left(x,y\right) = \left(-3,-3\right)\) The solution to the system of equations \(3x-4y=3\) and \(5x+3y=-24\) is \((-3,-3)\). Therefore, the correct choice is A. The solution set is \((-3,-3)\).

Respondido por UpStudy AI y revisado por un tutor profesional

error msg
Explicar
Simplifique esta solución

The Deep Dive

To solve the system using the addition method, we first need to manipulate the equations to eliminate one variable. Start with the original equations: 1. \(3x - 4y = 3\) 2. \(5x + 3y = -24\) Let's multiply the first equation by 3 and the second equation by 4 to align coefficients for \(y\): - \(9x - 12y = 9\) (First equation multiplied by 3) - \(20x + 12y = -96\) (Second equation multiplied by 4) Now, add these two new equations: \((9x - 12y) + (20x + 12y) = 9 - 96\) This simplifies to: \(29x = -87\) Solving for \(x\): \(x = -3\) Now, substitute \(x = -3\) back into one of the original equations to find \(y\). Using the first equation: \(3(-3) - 4y = 3\) \(-9 - 4y = 3\) \(-4y = 12\) \(y = -3\) So, the solution set is \((-3, -3)\). A. The solution set is \{ (-3, -3) \}.

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad